Induction of cat-86 by chloramphenicol and amino acid starvation in relaxed mutants of Bacillus subtilis. - Ambulos, N P (1988)
The chloramphenicol acetyltransferase gene cat-86 is induced through a mechanism that is a variation of classical attenuation. Induction results from the destabilization of an RNA stem-loop that normally sequesters the cat-86 ribosome-binding site. Destabilization of the stem-loop is due to the stalling of a ribosome in the leader region of cat-86 mRNA at a position that places the A site of the stalled ribosome at leader codon 6. Two events can stall ribosomes at the correct location to induce cat-86 translation: addition of chloramphenicol to cells and starvation of cells for the amino acid specified by leader codon 6. Induction by amino acid starvation is an anomaly because translation of the cat-86 coding sequence requires all 20 amino acids. To explain this apparent contradiction we postulated that amino acid starvation triggers intracellular proteolysis, thereby providing levels of the deprived amino acid sufficient for cat-86 translation. Here we show that a mutation in relA, the structural gene for stringent factor, blocks intracellular proteolysis that is normally triggered by amino acid starvation. The relA mutation also blocks induction of cat-86 by amino acid starvation, but the mutation does not interfere with chloramphenicol induction. Induction by amino acid starvation can be demonstrated in relA mutant cells if the depleted amino acid is restored at very low levels (e.g., 2 micrograms/ml). A mutation in relC, which may be the gene for ribosomal protein L11, blocks induction of cat-86 by either chloramphenicol or amino acid starvation. We believe this effect is due to a structural alteration of the ribosome resulting from the relC mutation and not to the relaxed phenotype of the cells.